SEX EDUCATION MELALUI BIMBINGAN KELOMPOK DENGAN TEKNIK SOSIODRAMA - ANIK SUPRIYATI (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2022)
The existence of the COVID-19 pandemic, which requires the education process to be carried out online, ultimately creates its own problems, both in terms of educators, the learning process itself and also problems from students. In this case students become less controlled because there is no direct supervision from the teacher, while parents have many limitations in their supervision, in the area where the researcher teaches most of the parents migrate to the city so that students only live with their grandmothers/grandparents or other families. so that it is not too focused on supervising students, besides that with the existence of advanced technology (gadgets) it increasingly opens up opportunities for students to socialize and communicate in cyberspace. Currently, sexual activities are also growing, people can easily open pornographic sites, and can have sex virtually, and so on. It is these possibilities that prompted the author to carry out this research. Through group guidance services with sociodrama techniques, it is expected to be able to provide understanding to students about the dangers of free sex even though it is done virtually. This article is a Best Practice that has been carried out by researchers. The activity was carried out in 2 meetings, in the first meeting, group guidance was carried out with the material "Toxic Relationship" and the second meeting with the topic of Sex Education". Through this study, it was found that at the first meeting 100% of student activity in participating in the service was very good, at the second meeting which began with a sociodrama played by two participants, who played very well, and during this second meeting there were 2 students who looked different. , are more likely to be silent and less enthusiastic. And after the activity was over, the two students met with the researcher and told about their personal experiences about the harassment they experienced. This shows that group guidance activities with sociodrama techniques are able to increase students' understanding of sex education and can increase students' courage to talk about their problems, and can increase self-defense in relationships. ABSTRAK Adanya pandemic covid-19 yang mengharuskan proses pendidikan dilakukan secara daring, pada akhirnya menimbulkan permasalahan tersendiri, baik dari sisi pendidik, proses pembelajaran itu sendiri dan juga permasalahan dari siswa. Dalam hal ini siswa menjadi kurang terkontrol karena tidak ada pengawasan secara langsung dari guru, sedangkan orang tua memiliki banyak keterbatasan dalam pengawasannya, di daerah tempat peneliti mengajar sebagian besar orang tua merantau di kota sehingga, siswa hanya tinggal dengan nenek/kakek atau family lain, sehingga tidak terlalu focus dengan pengawasan terhadap siswa, selain itu dengan adanya teknologi canggih (gadget) semakin membuka peluang untuk siswa dapat bersosilisasi dan berkomunikasi di dunia maya. Saat ini kegiatan Seksual pun semakin berkembang, orang dapat dengan mudah membuka situs-situs porno, serta dapat melakukan sex secara virtual, dan lain-lain. Kemungkinan-kemungkinan inilah yang mendorong penulis unutuk melakukan penelitian ini. Melalui layanan bimbingan kelompok dengan teknnik sosiodrama diharapkan mampu memberikan pemahaman terhadap siswa tentang bahaya sex bebas meskipun dilakukan secara virtual. Artikel ini merupakan Best Practice yang pernah dilakukan oleh peneliti kegiatan dilaksanakan dalam 2 kali pertemuan, pada pertemuan pertama, bimbingan kelompok dilakukan dengan materi “Toxic Relationship” dan pertemuan kedua dengan topic Sex Education”. Melalui penelitian ini didapatkan hasil, pada pertemuan pertama 100% Keaktifan siswa dalam mengikuti layanan sangat baik, pada pertemuan kedua yang diawali dengan sosiodrama yang dimainkan oleh dua orang peserta, yang bermain dengan sangat baik, dan selama pertemuan kedua ini terdapat 2 siswa yang terlihat berbeda, lebih cenderung diam dan kurang bersemangat. Dan setelah kegiatan selesai ke dua siswa ini menemui peneliti dan bercerita tentang pengalaman pribadinya mengenai pelecehan yang dialaminya. Hal ini menunjukkan bahwa kegiatan bimbingan kelompok dengan teknik sosiodrama mampu meningkatkan pemahaman siswa tentang sex education dan dapat meningkatkan keberanian siswa untuk bercerita tentang permasalahan dirinya, serta dapat meningkatkan self defance dalam pergaulan.